Attraction of Cocoa Pod Borer to Non-Host Plant Carrot Leaves Extract - Firmansyah, Amanda Patappari; S, Sylvia; Alam, Gemini; Dewi, Vien Sartika (International Journal of Psychosocial Rehabilitation, 2020)
Carrot leaves are included as agricultural waste and have not been widely used especially as insect attractants. Carrot leaves content is known, including fatty acids, chlorogenic acid, and gallic acid which serves as a stimulant for Lepidoptera. Cocoa pod borer (CPB) is a moth of the Lepidoptera order that attacks cocoa plants and losses due to its attack can reach 82.2%. Control is difficult because CPB larvae are in the pod, therefore control is directed at adult insects. One alternative to control CPB by utilizing plant extracts as attractants. Therefore, this study aims to determine the ability of carrot leaves extract as an attractant of CPB. Carrot leaves are extracted by soaking the leaves with methanol 70% in stages with a comparison between the plants and solvents respectively (4:1,2:1,1:1). The results of the marinade are then evaporated with a rotary evaporator machine and then crude extract is made into several concentrations of 7%, 5%, 3%, and 1% for use in bioassays. Bioassay uses 2 cylinder cages; the first cylinder cage is made of 5 holes to be connected to the second cylinder through clear plastic pipes. 20 CPB imago consisting of 10 males and 10 females were inserted in the first cage cylinder, then carrot leaf extract was inserted in the second cage cylinder. Observations are made every 3 hours for 24 hours. The most visited extract was a concentration of 7%. Indications of interest in the CPB imago are based on the percentage of interest with a value of 82% or the "very high" category. The amount of imago is 43.75% and is significantly different from other treatments. The number of female CPB imago was more at an average value of 7.00 and significantly different from all concentrations and controls. While the number of male imago was not significantly different in all treatments. Imago CPB visited all extract treatments during the first 3 hours since the bioassay was carried out and conversely, no CPB was seen in the control.